Diversidade e sistemática dos transmissores das principais zoonoses de Sergipe - Dantas, José Oliveira (2006)
The study describes, under the view point of zoological systematics, the vectors involved in the main zoonosis of Sergipe and its distribution in the regional ecosystems. Additionally are commented related aspects to the etiologic agents, biology of the vectors, number of cases registered in Sergipe during 1999 2004 and the potential zoonosis. Animals belonging to 6 taxonomic orders are transmitters of zoonosis in Sergipe: Diptera (19 species), Hemiptera (9 species), Siphonaptera (7 species), Rodentia (3 species), Basomatophora (2 species) and Chiroptera (2 species). Restricted to the caatinga it were registered 5 species (Diptera 3, Hemiptera 2), 6 species are presented in the atlantic forest (Diptera 3, Hemiptera 3) and 31 species are distributed in both domains (Diptera 13, Hemiptera 4, Siphonaptera 7, Basomatophora 2, Rodentia 3 and Chiroptera 2). Artificial Identifications keys for recognizing orders, families, subfamilies, genus and species are presented. The main zoonosis presented in Sergipe are the classic and hemorrhagic dengue fever, cutaneous and visceral leishmaniosis, Chagas disease, schistossomosis and leptospirosis.The potential zoonosis are the urban yellow fever, malaria, filariosis, and human pest. It was not detected endemic zoonosis in the region; restricted to the northeast focuses are the Chagas disease and schistossomosis. The others zoonosis occur in all regions.